Aldehyde dehydrogenase 2 activation in aged heart improves the autophagy by reducing the carbonyl modification on SIRT1 - Wu, Bing (Oncotarget, 2016)
Cardiac aging is characterized by accumulation of damaged proteins and decline of autophagic efficiency. Here, by forestalling SIRT1 carbonylated inactivation in aged heart, we determined the benefits of activation of aldehyde dehydrogenase 2 (ALDH2) on the autophagy. In this study, the ALDH2 KO mice progressively developed age-related heart dysfunction and showed reduction in the life span, which strongly suggests that ALDH2 ablation leads to cardiac aging. What's more, aged hearts displayed a significant decrease ALDH2 activity, resulting in accumulation of 4-HNE-protein adducts and protein carbonyls, impairment in the autophagy flux, and, consequently, deteriorated cardiac function after starvation. Sustained Alda-1 (selective ALDH2 activator) treatment increased cardiac ALDH2 activity and abrogated these effects. Using SIRT1 deficient heterozygous (Sirt1+/−) mice, we found that SIRT1 was necessary for ALDH2 activation-induced autophagy. We further demonstrated that ALDH2 activation attenuated SIRT1 carbonylation and improved SIRT1 activity, thereby increasing the deacetylation of nuclear LC3 and FoxO1. Sequentially, ALDH2 enhanced SIRT1 regulates LC3-Atg7 interaction and FoxO1 increased Rab7 expression, which were both necessary and sufficient for restoring autophagy flux. These results highlight that both accumulation of proteotoxic carbonyl stress linkage with autophagy decline contribute to heart senescence. ALDH2 activation is adequate to improve the autophagy flux by reducing the carbonyl modification on SIRT1, which in turn plays an important role in maintaining cardiac health during aging.